Predictors of early school leaving in within teaching through interaction framework - Medveckis, Arturs; Pigozne, Tamara; Birzina, Rita; Pelnena, Ivita (Frontiers in Education, 2025)
AimThe aim of the research is to identify and to analyse the possibilities of early school leaving support and predictive factors related to emotional and learning support and classroom organization.MethodsBased on the Teaching through Interactions Framework, the study analyses the socio-emotional and methodological factors of early school leaving – emotional and learning support and classroom organization. In the analysis of theoretical scientific literature, a Systematic Review has been carried out, where the scientific articles included in internationally cited databases Web of Science, Scopus and Ebsco have been analysed by key words. Correlation and regression analysis in the SPSS environment of the program for processing quantitative data has been performed in a correlative study.ResultsThe findings of the correlation analysis show that there are statistically significant negative correlations between early school leaving and emotional and learning support, as well as classroom organization. The selected six articles are mostly focused on the emotional support provision. As a result of the regression analysis, the most significant factor predicting early school leaving has been identified - the lack of emotional support.ConclusionScientific articles included in the WoS, Scopus and Ebsco databases do not use a holistic approach to preventing early school leaving. The lower the emotional, classroom organization and instructional support, the higher the risk of early school leaving. Teacher’s empathy and sensitivity to the academic, socio-emotional and developmental needs of individual students and the whole class are the most important predictors of early school leaving.